Keamanan Produk Pangan Yang Dijual Melalui Media Sosial Dalam Perspektif Perlindungan Konsumen - Pesulima, Theresia Louize; Sopamena, Ronald Fadly (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
People who consume unsafe food products can endanger their health and even their lives. However, the fact is that until now these unsafe food products are still a problem that must be faced by the state. This becomes even more difficult when many food products can be found easily through social media. So that business actors can promote and market food products without a permit so that it has the potential to harm consumers. The research method used in this research is normative juridical or known as legal research which is carried out by studying and analyzing the substance of laws and regulations on the subject matter or legal issues in consistency with existing legal principles. The government can supervise or cooperate with social media managers to identify food products that do not have a permit. Repressive protection can be provided by the government by providing strict sanctions for business actors who produce food products without certification. Sanctions for business actors who ignore consumer rights include criminal sanctions and fines as well as revocation of business licenses. Thus, legal protection for consumers who consume food products distributed through social media can be more effective so that consumers are not harmed.